PENGARUH KECERDASAN EMOSI TERHADAP KINERJA PEGAWAI DENGAN AMBIGUITAS PERAN SEBAGAI VARIABEL INTERVENING - Kristianingsih, Tri Puji; Darmastuti, Ismi (Faculty of Economics and Business Diponegoro University, 2015)
The performance of the employees have an important role in achieving the success of a company, the employee acts as a planner and executor of the company's goals. Employee performance is affected by many factors such as emotional intelligence and role ambiguity. This study aimed to analyze the influence of emotional intelligence, role ambiguity on performance. The negative impact caused by the ambiguity of roles can degrade the performance of the employee. The employees who experience role ambiguity, the results of his work was not optimal. Emotional intelligence employees can improve employee performance.The study population was all nurses General Hospital Semarang as much as 269 nurses. The sampling technique using a convenience sampling technique, with a total sample of 75 nurses and using multiple regression analysis with SPSS.The results of hypothesis testing, showed that emotional intelligence variables negatively affect the role ambiguity and ambiguity variables negatively affect performance. Emotional intelligence variable positive effect on performance.